Integrating Pharmacology and Microbial Network Analysis with Experimental Validation to Reveal the Mechanism of Composite Sophora Colon-Soluble Capsule against Ulcerative Colitis. (20th April 2020) - Ding, Yuxuan; Chen, Mingjun; Wang, Qiying; Gao, Lu; Feng, Yang; Wang, Shida; Song, Zitian; Tong, Zhanqi
Abstract : Ulcerative colitis (UC) has multifactorial pathogenesis that acts synergistically, such as immune system dysregulation and expansion of infectious gut microbiota. Therefore, a multicomponent treatment derived from Chinese herbal medicine that interacts with multiple targets synergistically is needed. Composite sophora colon-soluble capsule (CSCC) is a Chinese herbal formula that has shown therapeutic efficacy against UC in randomized clinical trials. However, its bioactive components and potential target genes against UC remain unclear. Here, we used a network pharmacology approach to detect component-target-pathway interactions of CSCC against UC. A total of 29 gene targets, 91 bioactive components, and 20 enriched pathways of CSCC were identified. The IL-17 signaling pathway activated by infectious gastrointestinal microbes and predicted by the network analysis to be a major pathway modulated by CSCC against UC was studied in a dextran sulfate sodium-induced colitis model. CSCC showed remarkable efficacy against UC with respect to the attenuation of colon length, body weight loss, and disease activity index through gut microbiota recovery and intestinal immune homeostasis. The rectal administration of CSCC reduced the numbers of Th17 cells isolated from both mesenteric lymph nodes and lamina propria mononuclear cells and the levels of IL-17A, IL-6, IL-1 β, and TNF- α . Additionally, the percentage of Treg cells and the levels of their hallmark cytokines were upregulated. Rectal administration of CSCC led to microbiota regulation with a significant correlation between suppression of Verrucomicrobiaceae and Ruminococcaceae, as well as the elevation of Lactobacillaceae, and CSCC administration via microbiome correlation heatmaps and cooccurrence network analysis at multiple time points. Thus, our study presents an effective herbal formula, CSCC, for UC treatment and explores its components and mechanisms of efficacy through the examination of gut microbiota and hallmark cytokines in the IL-17 pathway.